2013
DOI: 10.2486/indhealth.2012-0108
|View full text |Cite
|
Sign up to set email alerts
|

Critical Body Temperature Profile as Indicator of Heat Stress Vulnerability

Abstract: Extreme climatic heat is a major health concern among workers in different occupational pursuits. People in the regions of western India confront frequent heat emergencies, with great risk of mortality and morbidity. Taking account of informal occupational groups (foundry and sheet metal, FSM, N=587; ceramic and pottery, CP, N=426; stone quarry, SQ, N=934) in different seasons, the study examined the body temperature profiling as indicator of vulnerability to environmental warmth. About 3/4th of 1947 workers h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…Physiological parameters have previously been found to be indicators of productivity loss. For example, Nag et al found that when the core temperature reaches 38°C, if the worker is able to self-pace, s/he will adjust the pace and slow down (5). This translates into an automatic productivity loss.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Physiological parameters have previously been found to be indicators of productivity loss. For example, Nag et al found that when the core temperature reaches 38°C, if the worker is able to self-pace, s/he will adjust the pace and slow down (5). This translates into an automatic productivity loss.…”
Section: Methodsmentioning
confidence: 99%
“…A natural reaction of a working person to heat is to reduce physical activity, which reduces the body’s internal heat production (25) . An outcome of this natural preventive mechanism is reduced work capacity, which results in lower productivity (2).…”
mentioning
confidence: 99%
“…A study in Ahmedabad on other occupations showed that workers' perceptions of heat load and reports of heat related disorders were significant and correlate with the physical findings at the workplace. [ 12 ] The same study concluded that occupational groups exposed to direct solar radiation have increased risk of heat injury. In addition, extreme temperatures in Ahmedabad have been documented to have health effects on the general population.…”
Section: Introductionmentioning
confidence: 99%
“…This special issue of Industrial Health presents papers on different aspects of occupational heat problems in relation to climate change. The papers present examples from different parts of the world, and highlight methods for heat exposure assessment 11) , standards for occupational heat exposures 12,13) , and the health and productivity risks of workplace heat in relation to climate conditions and climate change 14) . A small scientific conference on "Occupational heat exposure indicators for use in climate change impact assessments" was held in Lund, Sweden, in August 2012, and many of the papers in this collection are based on presentations in Lund.…”
mentioning
confidence: 99%